Reasons for children’s motor activity practices in school - Berleze, Adriana; Vieira, Lenamar Fiorese; Krebs, Ruy Jornada (Journal of Physical Education (Maringá), 2008)
This study aims at investigating the reason children (from 8 to 10 years old of private school in Santa Maria-RS) have for practicing motor acitivities in school. 88 children (45 girls and 43 boys) from primary school were studied and a questionnaire based on Roberts et al., 1986 was used. In order to collect the data the questionnaire was answered in group in the classroom. For the analysis of data the descriptive statistics and internal (task and ego) and external ( social approval and extrinsical reward) categories were employed. Results showed that concerning female children’s motivation for the practice of motor acitivities, internal reasons related to ego were mostly frequent and the entertainment and recreation seem to be the relevant ones for the group; as for male participants’ reasons the internal ones were also the most evident but related to task, pleasure on performing movement, the liking for sports and the learning in Physical Education classes were the most important reasons. Comparing internal and external reasons for the motor practices, the internal reasons were more frequent. Thus, there are evidences that children are interested in task and ego, demonstranting that school context, in its physical and human structure, seems to provide opportunities to perform such motor activities as well as to encourage and to teach.